Flexural Behaviour of Waste-based Natural Fibre Reinforced Composite from Palmyra Fibre and Waste Polythene - Wijesena, P.C.M.; Karunarathna, D.M.S.M.; Somarathna, H.M.C.C. (University of Jaffna, 2022)
In recent years researchers are focusing on manufacturing new products by using wastes as raw materials. Among them, the products which are developed using natural fibre wastes have gained substantial attention due to their excellent properties. This research is conducted to investigate the feasibility of producing waste-based Natural Fibre Reinforced Composites (NFRC) using Palmyra fibre as reinforcement material and waste Low Density Polyethylene (LDPE) as the matrix. To check the effect of fibre length and the fibre content on the flexural performance, two fibre lengths (20 mm, and 40 mm), and three fibre volume fractions (15%, 20%, and 25%) were used. The Hand lay-up process was used to manufacture the waste-based NFRC. A hot press machine and a cold press machine were used to prepare the moulded waste-based NFRC sheets. The flexural properties of the NFRCs were significantly influenced by the content of Palmyra fibre. According to the overall findings obtained, 15% of reinforcement content with having 40mm length of fibre can be identified as the optimum conditions to fulfil the required outcomes of this research with desirable mechanical properties.
Keywords: Waste-based natural fibre reinforced composites; Palmyra; Low-density polyethylene; Waste management; Sustainability